1991
DOI: 10.1103/physreva.44.2625
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a plasma column produced and sustained by a traveling electromagnetic wave in the presence of a constant axial magnetic field

Abstract: We present the basic equations for modeling a plasma column produced and sustained by a traveling electromagnetic wave in the presence of a constant external magnetic field. The model consists of two equations -a local-dispersion relationship and a wave-energy-balance equation -and a relation between the absorbed wave power per unit length averaged across the column (proportional to the squared-wave electric field) and the local electron number density. The dispersion relation and the balance equation are deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 29 publications
1
37
0
Order By: Relevance
“…In such consideration the dimensionless plasma density N in the region just near to the generator can be determined from the phase diagrams for the fixed azimuth wavenumber m and dimensionless parameters σ and Ω. The used discharge model allows one to compare the axial plasma density profiles of the discharges, sustained by the waves with arbitrary azimuth wavenumber m. It is necessary to mention that axial profiles of plasma density in the discharges sustained by the waves in symmetric (m = 0) and dipolar (m = −1) modes determined by means of this model are in good agreement with the results obtained by other research groups (see, for example, [5,7,8]). Also it is necessary to stress that this consideration is valid when axial variations of plasma density n, axial wavenumber k 3 and wave field amplitudes are slow enough to consider the locally uniform approximation.…”
Section: Axial Structure Of the Dischargesupporting
confidence: 58%
See 2 more Smart Citations
“…In such consideration the dimensionless plasma density N in the region just near to the generator can be determined from the phase diagrams for the fixed azimuth wavenumber m and dimensionless parameters σ and Ω. The used discharge model allows one to compare the axial plasma density profiles of the discharges, sustained by the waves with arbitrary azimuth wavenumber m. It is necessary to mention that axial profiles of plasma density in the discharges sustained by the waves in symmetric (m = 0) and dipolar (m = −1) modes determined by means of this model are in good agreement with the results obtained by other research groups (see, for example, [5,7,8]). Also it is necessary to stress that this consideration is valid when axial variations of plasma density n, axial wavenumber k 3 and wave field amplitudes are slow enough to consider the locally uniform approximation.…”
Section: Axial Structure Of the Dischargesupporting
confidence: 58%
“…The increase of external magnetic field value leads to considerable growth of the dimensionless plasma density and dimensionless discharge length, especially in the second stability region. Similar influence of external magnetic field on plasma parameters can be observed in gas discharges, which are sustained by the SW in dipolar mode [5,7,8]. It is necessary to mention that with the increase of external magnetic field value Ω the length of the discharge in the second stability region substantially exceeds the length of the discharge in the first stability region at the same external discharge parameters (approximately in four times for Ω = 3.0, see Fig.…”
Section: Axial Structure Of the Dischargementioning
confidence: 65%
See 1 more Smart Citation
“…In the limit of infinite B field, all waves become TM modes, whatever the mode number is, and can be identified as a pure pseudosurface wave or volume waves. 9 Benova et al 10 recently calculated the three-dimensional surface and pseudosurface waves structure numerically for finite B field. They used an electromagnetic model consisting of a dispersion relation and an energy balance equation.…”
Section: Introductionmentioning
confidence: 99%
“…The gas discharges produced and sustained by electromagnetic waves propagating along the axial direction in the discharge chambers with cylindrical geometry are investigated both in the isotropic [2][3][4][5][6] and in the magnetoactive waveguides [7][8][9][10]. It is found that application of the external magnetic field facilitates the plasma production and makes the discharge region longer [8].…”
Section: Introductionmentioning
confidence: 99%